FORMULATION AND ACTIVITY TESTS OF EUPHATORIUM LEAF (Euphatorium oradatum L.) ETHANOL EXTRACT GEL ON BURNS HEALING OF RABBITS - Firmansyah, Firmansyah; Taufiq; Hafid, Muliana; Sari, Alfiani; Duppa, Muhammad Taufiq (Poltekkes Kemenkes Surakarta, 2024)
A gel is a semisolid system consisting of small inorganic particles or large organic molecules suspended in a liquid. This study aims to determine if Euphatorium leaf extract can be formulated into a gel preparation that meets the physical quality requirements and to determine the activity of Euphatorium leaf extract gel on rabbit burn wound healing. This type of research was a laboratory experiment with gel preparation formulations and activity tests on rabbit burn wound healing. Preparation of Euphatorium leaf extract by maceration with 96% ethanol solvent. In this study, FI gel preparations (negative control), FII (2.5% extract), FIII (5% extract), FIV (10% extract), FV (Bioplacenton positive control). Furthermore, a physical stability test was carried out on the Euphatorium leaf extract gel which included; organoleptic test, homogeneity test, pH test, spreadability test, adhesion test, viscosity test and accelerated stability test. Then tested the activity of Euphatorium leaf extract gel on the healing of rabbit burns. In this test, 5 rabbits were used. Each rabbit was made a wound with an area of ​​2 cm on the back area which was divided into 3 wound areas. Each wound area is given the same concentration. Observations were made every 3 days of treatment. The results showed that Euphatorium leaf extract could be formulated into a gel preparation and met the physical stability requirements of the gel, and the activity test on the healing of rabbit burns obtained an average percentage of burn wound healing, namely FI (11.83%), FII (24.50) , FIII (31.33%), FIV (54.17%) and FV (66.17%). Based on the results of statistical analysis tests with one way ANOVA, it was shown that there were significant differences in the healing activity of rabbit burns between all treatment groups where the value of p <0.05.